Mengisahkan Ziarah Eksodus Melalui Eskterior Bangunan Gereja - Rasid Rachman (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2021)
The exterior of Church building is the clearest face of the community of its members because it is openly showed by anybody. It is not only evidence of the very art and historical heritage but also a content of theological narrative and re-narrative of Church role in the world. This writing will show that there is a theological narrative behind the Church building. In this writing, that theological narrative is limited to the story of the journey and the sojourn of the Israel people in the wilderness to the promised land. From the exodus narrative, I renarrate the role of the Church in the context where it lives. This writing used the theory of bottom with three elements, namely: concept, category, and proposition. The early concept is the exodus narrative according to the Bible. Catching the category, this exodus concept will be anriched by the blended with the narrative of some Church buildings in Indonesia, theology of the Old Testament and liturgy, the anthropology of culture, and the philosophy of architecture. The result of this research is renarrative of the living Church buildings. The proposition is an offer on an interrelation between Biblical narrative, a historical roll of the Church building, and the renarrative or the storytelling renewal, with the present of Church mission. Eksterior bangunan gereja adalah wajah paling jelas persekutuan anggotanya, sebab terlihat secara terbuka oleh siapa pun. Ia bukan hanya bukti mahakarya seni arsitektur dan peninggalan sejarah, tetapi juga berisi narasi teologis dan merenarasikan peran gereja di dunia. Tulisan ini ingin memperlihatkan bahwa ada narasi teologi di balik eksterior bangunan gereja. Dalam tulisan ini, narasi teologi tersebut dibatasi pada kisah perjalanan dan persinggahan umat Israel di padang gurun menuju tanah perjanjian. Dari narasi eksodus tersebut, saya merenarasikan peran gereja di dalam konteksnya.Tulisan ini menggunakan teori dari bawah dengan tiga unsur, yaitu: konsep, kategori, dan proposisi. Konsep awal adalah narasi eksodus sebagaimana kesaksian Alkitab. Untuk mencapai kategori, konsep eksodus ini akan diperkaya dengan memadukan narasi beberapa bangunan gereja di Indonesia, teologi Perjanjian Lama dan liturgi, antropologi budaya, dan filsafat arsitektur. Hasil penelitian adalah renarasi bangunan gereja yang hidup. Proposisi berupa tawaran akan hubungan-hubungan antara narasi Alkitab, guliran historis bangunan gereja berdiri, dan renarasi atau pembaruan penceritaan, dengan misi gereja kini.